"Some convincing arguments to pass back to nervous customers": the role of the tobacco retailer in the Australian tobacco industry's smoker reassurance campaign 1950–1978. (26th November 2003) - Tofler, A; Chapman, S
Abstract : Background: Epidemiological studies and reports on smoking and health published in the 1950s and 1960s threatened the tobacco industry worldwide, which acted to reassure smokers and counteract mounting evidence that smoking posed a serious risk to smokers' health. Objective: To document the use of tobacco retailers (1) as a conduit to pass messages of reassurance onto smokers, and (2) to recruit youth and women into smoking. Methods: Review of an extensive collection of Australian tobacco retail trade journals (1950–1978) for articles consistent with the industry's efforts to counter messages about smoking and health, and how to attract non-smokers, particularly youth and women. Results: The main arguments advanced in the journals included the notion that air pollution and other substances cause cancer, that "statistics" did not constitute proof in the tobacco health scare, and that the industry was committed to research into the causes of cancer and into developing a "safer" cigarette. Conclusions: Numerous articles designed to be reiterated to customers were published, arguing against the link between tobacco and ill health. Tobacco retailers, salesmen and retail trade organisations played a significant role in dissembling the tobacco health nexus. Tobacco retail journals may be an important component in tobacco industry misinformation strategies.